Mutation update: TGFBI pathogenic and likely pathogenic variants in corneal dystrophies. Issue 6 (28th March 2019) - Kheir, Valeria; Cortés‐González, Vianney; Zenteno, Juan C.; Schorderet, Daniel F.
Abstract: Human transforming growth factor β‐induced ( TGFBI ), is a gene responsible for various corneal dystrophies. TGFBI produces a protein called TGFBI, which is involved in cell adhesion and serves as a recognition sequence for integrins. An alteration in cell surface interactions could be the underlying cause for the progressive accumulation of extracellular deposits in different layers of the cornea with the resulting changes of refractive index and transparency. To this date, 69 different pathogenic or likely pathogenic variants in TGFBI have been identified in a heterozygous or homozygous state in various corneal dystrophies, including a novel variant reported here. All disease‐associated variants were inherited as autosomal‐dominant traits but one; this latter was inherited as an autosomal recessive trait. Most corneal dystrophy‐associated variants are located at amino acids Arg124 and Arg555. To keep the list of corneal dystrophy‐associated variant current, we generated a locus‐specific database for TGFBI (http://databases.lovd.nl/shared/variants/TGFBI ) containing all pathogenic and likely pathogenic variants reported so far. Non‐disease‐associated variants are described in specific databases, like gnomAD and ExAC but are not listed here. This article presents the most recent up‐to‐date list of disease‐associated variants.